Estudio de tiempos improductivos en el proceso de ovillado de la producción de piolas y cordeles de la empresa Cordeplast de la ciudad de Ambato - Nata Ichina, Holger Fabricio (2022)
The purpose of this research project is a time study in the company Cordeplast S.A. dedicated to the production of polyester-based ropes for agricultural and hardware use, in two presentations 1H and H17. The study begins with an exploratory investigation to identify the problems present in the production process; for this purpose, the Ishikawa diagram was used to find the causes of bottlenecks, unproductive times, unnecessary displacements and delays in the delivery of orders to the customer. Next, we proceeded to characterize the different subprocesses with their corresponding activities through the elaboration of flow charts and analytical flowcharts, then we proceeded to develop the time study by taking 10 samples of each activity and using the nomographic method, In addition to the zero regression technique, a stopwatch, a digital camera, a record sheet and the direct observation technique were used to record times. Also, based on the recommendations of the ILO, the most experienced worker in the production process was selected, resulting in a cycle time of 19.01 min. for the manufacture of the 1H pipe. Finally, we proceeded with the formulation of the proposal to improve the production process. In which we considered as an alternative the redesign of the plant using the SLP (Systematic Layout Planning) methodology and software (Corelap 01), the combination of activities and the calculation of the number of operators per production line, which allowed us to reduce the cycle time by 8.06 min for the H1 pipe, In addition, to validate the results obtained, a simulation of the production process was carried out using FlexSim software, which confirmed the increase in production by 18 bales of 20 balls, generating an increase in productivity of 28%, increasing monthly income by $5,616 dollars